Human 343delT HSPB5 chaperone associated with early-onset skeletal myopathy causes defects in protein solubility. - Mitzelfelt, K; Limphong, P; Choi, M; Kondrat, F; Lai, S; Kolander, K; Kwok, W; Dai, Q; Grzybowski, M; Zhang, H; Taylor, G; Lui, Q; et al. (American Society for Biochemistry and Molecular Biology, 2016)
Mutations of HSPB5 (also known as CRYAB or αB-crystallin), a bona fide heat shock protein and molecular chaperone encoded by the HSPB5 (crystallin, alpha B) gene, are linked to various multisystem disorders featuring variable combinations of cataracts, cardiomyopathy, and skeletal myopathy. This study aims at investigating the pathological mechanisms involved in an early onset myofibrillar myopathy manifesting in a child harboring a homozygous recessive mutation in HSPB5, 343delT. To study HSPB5 343delT protein dynamics, we utilize model cell culture systems including induced pluripotent stem cells (iPSCs) derived from the 343delT patient (343delT/343delT) along with isogenic, heterozygous, gene-corrected control cells (WT KI/343delT), and BHK21 cells, a cell line lacking endogenous HSPB5 expression. 343delT/343delT and WT KI/343delT iPSC-derived skeletal myotubes (iSKMs) and cardiomyocytes (iCMs) did not express detectable levels of 343delT protein, contributable to extreme insolubility of the mutant protein. Overexpression of HSPB5 343delT resulted in insoluble mutant protein aggregates and induction of a cellular stress response. Co-expression of 343delT with WT prevented visible aggregation of 343delT and improved its solubility. Additionally, in vitro refolding of 343delT in the presence of WT rescued its solubility. We demonstrate an interaction between WT and 343delT both in vitro and within cells. These data support a loss of function model for the myopathy observed in the patient, as the insoluble mutant would be unavailable to perform normal functions of HSPB5, though additional gain-of-function effects of the mutant protein cannot be excluded. Additionally, our data highlights the solubilization of 343delT by WT, concordant with the recessive inheritance of the disease and absence of symptoms in carrier individuals.